Seventh son - Delaney, Joseph, 1945- (Delaney, Joseph, 1945- Last apprentice, 2005)
"The powers of evil are strengthening, and only one man holds them back. Now that man needs an apprentice. Tom Ward is the seventh son of a seventh son, and he has been chosen. When one of the world's most malevolent witches escapes, Tom will face his first test. Many apprentices have come before. They have failed, or fled, or died. If Tom succeeds--and if he survives--he'll be the last apprentice"--Back cover.